TINJAUAN YURIDIS KEDAULATAN NEGARA TERHADAP PENGGUNAAN MATA UANG ASING DI WILAYAH PERBATASAN NEGARA KESATUAN REPUBLIK INDONESIA - Elisabeth, Sandy; Deliana, Evi; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The sovereignty of a country is the highest power of the country to rule andenforce the law in its territory. Including with power in regulating the economicsystem and the use of currencies imposed in the territory of the country. This isdue to today's modern society, the mechanism of the economy based on the trafficof goods and services of all economic activities will require money as a means ofsmoothing to achieve its objectives. Problem that arises in the use of money is thatthe use of foreign currency in the borders of the Republic of Indonesia is stillwidely practiced. So that the sovereignty of a country finds intervention due to theuse of foreign money. Bank Indonesia as the central bank has duties, one of whichis to keep the value of the rupiah stable. The rupiah regulation in order to remainstable has been followed up in Law Number 7 of 2011 concerning Currency. Inaddition International Regulations governing the economic sovereignty of acountry are discussed in Articles 1, 2 (paragraph 1), 7 and 10. The Montevideo1933 Convention concerning the Rights and Obligations of the State explain thejurisdiction of a country's sovereignty.The writing of this thesis uses normative legal research method with libraryresearch data collection, that is by examining library material or secondary datain the form of primary legal materials namely related regulations, secondary legalmaterials namely related documents and tertiary law which is an indication ofprimary and secondary legal materials. Secondary data that has been compiled isthen analyzed using qualitative methods to obtain conclusions.Exceptions to the use of the Rupiah Currency regulated in Article 21paragraph 2 of Act Number 7 of 2011 concerning Currency are certaintransactions in the context of implementing the budget and state revenues andexpenditures, receiving or granting grants from or abroad, international tradetransactions, deposits at banks in the form of foreign currency, and internationalfinancing transactions. Related to the use of the Rupiah Currency regulated inArticle 21 of 2011 is a tool for the purpose of payment, settlement of otherobligations carried out in the Territory of the Republic of Indonesia.